Language and identity politics a cross-Atlantic perspective - Spati, Christina (New York Berghahn Books, 2016)
In an increasingly multicultural world, the relationship between language and identity remains a complicated and often fraught subject for most societies. The growing political salience of questions relating to language is evident not only in the expanded implementation of new policies and legislation, but also in heated public debates about national unity, collective identities, and the rights of linguistic minorities. By taking a comprehensive approach that considers both the inclusive and exclusive dimensions of linguistic identity across Europe and North America, the studies assembled here provide a sophisticated look at one of the global era's defining political dynamics.
Figures and tables -- Acknowledgements -- Introduction. Language and the rise of identity politics ; An Introduction / Christina Spati -- Part I. Language and identity politics: theory and concepts -- Chapter 1. Language and collective identity: theorising complexity / Peter Ives -- Chapter 2. The politics of linguistic identity in Europe: between the expression of power and the power of expressivity / Peter A. Kraus -- Part II. Language and collective identity in multilingual states -- Chapter 3. Language and identity politics in Belgium / Claude Javeau -- Chapter 4. Plurilingualism and identity politics: the case of Switzerland / Christina Spati -- Chapter 5. Languages and collective identities in Switzerland: the case of bilingual cantons (Bern, Fribourg, Valais) / Manuel Meune -- Chapter 6. Language rights and language endangerment in Canada: the case of indigenous languages / Donna Patrick -- Part III. Language and identity politics in immigration societies -- Chapter 7. Immigrants and the reframing of language and national identity politics in the United States / Ronald Schmidt, Sr. -- Chapter 8. Challenges of diversity: language and immigration in Switzerland / Damir Skenderovic -- Chapter 9. Language and the transformation of identity politics in minority francophone communities in Canada: between collective linguistic identity and individualistic integration policies / Nicole Gallant -- Conclusion. The problematic nexus of language and identity: some concluding remarks / Robert Gould -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: Language and languages -- Political aspects; Language and culture -- Political aspects; Identity politics; Intercultural communication; Sociolinguistics